UMS PPKn Students' Perceptions of Commucation Ethics on Social Media - Sabrina, Alma Putri; Patmisari, Patmisari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The objective of this study is to determine how game addiction and the school environment affect the emotional development of students at Karanganyar High School (SMA). The study seeks to understand the joint influence between internal (gaming addiction) and external (school environment) factors on emotional development, which may be more complex than the influence of either factor alone. Methodology: The research method used is a quantitative correlation approach. Data were collected using a questionnaire consisting of 51 statements. The sample included 263 students from various high schools (SMA) across Karanganyar. Data analysis involved prerequisite tests (normality, multicollinearity, and heteroscedasticity) and hypothesis testing using multiple regression, F-test, and coefficient of determination. Results: The study shows that game addiction (X1) has a positive and significant effect on emotional development, with a significance value of 0.000 < 0.05 and a t-value of 3.682 > t-table (1.969). Similarly, the school environment variable (X2) also has a positive and significant effect, with a significance value of 0.000 < 0.05 and a t-value of 14.911 > t-table (1.969). The F significance value is 0.000 < 0.05 and the Adjusted R Square value is 0.558, indicating that 55.8% of the variation in emotional development is explained by the two variables, while 44.2% is influenced by other factors. Findings reveal that online game addiction can hinder emotional intelligence (e.g., alexithymia), while a positive school environment (e.g., teacher support, extracurriculars) can foster emotional well-being. Applications/Originality/Value: This study provides a novel perspective by emphasizing the emotional impact of gaming addiction, rather than the commonly studied academic impacts. It highlights the school environment as either a protective or risk factor, offering practical insights for educational institutions to support students’ emotional development. This dual focus on internal and external influences adds depth to the understanding of emotional health among adolescents.